On the ease of being green: An investigation of the inconvenience of electric vehicle charging. (15th January 2020) - Dixon, James; Andersen, Peter Bach; Bell, Keith; Træholt, Chresten
Highlights: The inconvenience of charging electric vehicles (EVs) is quantified by its time penalty. Idealised charging schedules are derived from over 39, 000 week-long travel diaries. Convenience parity occurs when EV charging carries the same time penalty as petrol car fuelling. Drivers who cannot charge at home are expected to suffer significant inconvenience. Very few long journeys are delayed due to charging if natural breaks are taken as recommended. Abstract: This paper presents a quantitative investigation of the inconvenience of electric vehicle (EV) charging relative to internal combustion engine vehicle (ICEV) fuelling in terms of the time penalty likely to be experienced by drivers. A heuristic approach to deriving idealised charging schedules from over 39, 000 week-long travel diaries from the UK National Travel Survey is presented in order to quantify the expected convenience parity — the point at which EV charging and ICEV fuelling are of comparable convenience — for combinations of battery capacity, charger power and access to charging at different locations (home, workplace and public destinations). It was found that although the majority — up to 95% — of individuals who can charge at home are expected to be able to reach convenience parity with battery sizes currently available in EV models at the 'affordable' end of the market, this is significantly less likely for those who rely on workplace or public charging — and particularly for those who must rely solely on en route charging. These individuals are expected to suffer considerable inconvenience associated with EV charging relative to ICEV fuelling, and although greater battery capacities and charger power ratings are expected to lessen this inconvenience, there remains a significant gap in the convenience of EV ownership between those who can charge while parked at home and those who cannot. Further analysis is carried out to long journeys that cannot be made on a single charge; 'range anxiety' being a major obstacle to widespread EV adoption. It was found that if drivers are compliant with the UK Highway Code in taking regular breaks on long journeys, fewer than 0.01% of trips are expected to be delayed by charging when using battery capacities of 40–60 kWh.